2015
DOI: 10.1021/acs.biochem.5b00018
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Drug Transport Pathways through Human P-Glycoprotein

Abstract: P-glycoprotein (P-gp) is a plasma membrane efflux pump that is commonly associated with therapy resistances in cancers and infectious diseases. P-gp can lower the intracellular concentrations of many drugs to subtherapeutic levels by translocating them out of the cell. Because of the broad range of substrates transported by P-gp, overexpression of P-gp causes multidrug resistance. We reported previously on dynamic transitions of P-gp as it moved through conformations based on crystal structures of homologous A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
103
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(114 citation statements)
references
References 80 publications
8
103
3
Order By: Relevance
“…The candidate residues identified using this approach were in broad agreement with those identified from docking and MD simulation based studies [20,34,35]. Another investigation using a large number of P-gp isoforms adopted a different approach using arginine enhancer mutations to identify residues within the translocation pathway [36].…”
Section: Discussionsupporting
confidence: 63%
“…The candidate residues identified using this approach were in broad agreement with those identified from docking and MD simulation based studies [20,34,35]. Another investigation using a large number of P-gp isoforms adopted a different approach using arginine enhancer mutations to identify residues within the translocation pathway [36].…”
Section: Discussionsupporting
confidence: 63%
“…Interestingly, the process by which Rhodamine‐123 interact with the NBD1 transmission interface may help to explain why several thioamide‐containing derivatives of Rhodamine‐123 can promote calcein‐AM uptake and inhibit vinblastine efflux with IC 50 s of ~2 μM . A different study also identified a possible site for tariquidar binding close to the ICL2/ICL3 region (TMD4/TMD9, site 1), together with two other sites located in the internal drug‐binding pocket (sites 2 and 3) . However, recent biochemical studies showed that tariquidar probably binds to sites 2 and 3 rather than to site 1, stabilizing the N ‐terminal domain, thus being able to block conformational changes leading to efflux and also rescue folding‐defective mutants …”
Section: Targeting Signal Transductionmentioning
confidence: 99%
“…146 A different study also identified a possible site for tariquidar binding close to the ICL2/ICL3 region (TMD4/TMD9, site 1), together with two other sites located in the internal drug-binding pocket (sites 2 and 3). 147 However, recent biochemical studies showed that tariquidar probably binds to sites 2 and 3 rather than to site 1, stabilizing the N-terminal domain, thus being able to block conformational changes leading to efflux and also rescue folding-defective mutants. 148 The ability of drugs to spontaneously bind to the cytosolic P-gp domains was also addressed recently by several independent studies ( Figure 6).…”
Section: Targeting Signal Transductionmentioning
confidence: 99%
“…[14] 2.6 | Cellular experiments 99m Tc-MIBI is a substrate for the P-gp pump. and exhaustiveness was set to 8 for the docking procedure so as to include all 12 helices.…”
mentioning
confidence: 99%